Sleep Quality Predicts Functional Disability in Older Adults with Low Back Pain: A Longitudinal Study. (November 2022) - Oliveira, Sabrina Dias; Pinto, Rafael Z.; Gobbi, Cynthia; Fernandes, Guilherme L.; Dokkedal-Silva, Vinícius; Lemes, Ítalo Ribeiro; Andersen, Monica L.; Tufik, Sergio; Lorenconi, Roselene Modolo Regueiro; Morelhão, Priscila K.
Low back pain (LBP) and sleep quality are two very prevalent complaints in the older population. However, little is known about the prognostic relationship between sleep quality and disability in older adults with LBP. The aim of this study was to examine the association between sleep quality and disability in older adults with LBP. This was a longitudinal study over a 6-month period. Older adults with LBP in the last 12 weeks and who had preserved cognitive functions were recruited. The questionnaires used were the Pittsburgh Sleep Quality Index and the Roland Morris Disability Questionnaire. At baseline, we collected information on demographic/anthropometric variables, cognitive status, depression, daytime sleepiness, and comorbidities. Linear regression adjusted for potential covariates were performed. Poor sleep at baseline predicted higher disability after 6 months [β = 0.30 (CI95%:0.07 to 0.55)]. Our results support the existence of an important relationship between sleep and disability in older adults with LBP.